2006
DOI: 10.3201/eid1203.051004
|View full text |Cite
|
Sign up to set email alerts
|

Host Feeding Patterns ofCulexMosquitoes and West Nile Virus Transmission, Northeastern United States

Abstract: Culex salinarius is a bridge vector to humans, while Cx. pipiens and Cx. restuans are more efficient enzootic vectors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
321
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 309 publications
(342 citation statements)
references
References 31 publications
(52 reference statements)
18
321
0
2
Order By: Relevance
“…pipiens as the primary enzootic vector in this region. Culex pipiens has been established as an important enzootic vector by consistent isolations of WNV from mosquito trap collections [11,13,20], by its ornithophilic feeding behaviour [13,40,41], and associations between virus-infected mosquitoes and dead bird reports [42][43][44][45][46]. This species has also been incriminated as a bridge vector in Illinois [47].…”
Section: Discussionmentioning
confidence: 99%
“…pipiens as the primary enzootic vector in this region. Culex pipiens has been established as an important enzootic vector by consistent isolations of WNV from mosquito trap collections [11,13,20], by its ornithophilic feeding behaviour [13,40,41], and associations between virus-infected mosquitoes and dead bird reports [42][43][44][45][46]. This species has also been incriminated as a bridge vector in Illinois [47].…”
Section: Discussionmentioning
confidence: 99%
“…Ornithophagic species within the genus Culex are important vectors and responsible for zoonotic WNV transmission among birds (Molaei et al 2006). Culex in California are quiescent or diapause during cold winter months (Nelms et al 2013a,b), and low temperatures hinder WNV replication within the overwintering mosquito hosts (Dohm et al 2002, Reisen et al 2006b).…”
mentioning
confidence: 99%
“…Our bioinformatic analysis revealed that there was too little sequence diversity among the targeted sequences for microarray differentiation. As a substitute, we chose to model our approach after a study by Molei and others 26 using target-specific PCR of the Cytb gene for identification. The benefit to using this model was the significant amount of avian and mammalian Cytb gene sequence data available.…”
Section: Discussionmentioning
confidence: 99%
“…The PCR amplification was accomplished using the Cytb avian-a (forward, GACTGTGA CAAAATCCCNTTCCA; reverse, GGTCTTCATCTYHGG YTTACAAGAC) 24 and mammalian-a (forward, CGAAGC TTGATATGAAAAACCATCGTTG; reverse, TGTAGTTR TCWGGGTCHCCTA) 25 primers as previously desribed. 26 Amplicons were visualized using 2% Agarose E-Gel gels (Invitrogen Inc.). Biotin labeling and post-PCR purification.…”
Section: Methodsmentioning
confidence: 99%